Konsep Diri Korban Kekerasan Seksual dalam Perspektif Komunikasi Intrapersonal - Rumaisha Alwi, Zulaikha; Fitriani, Dinda Rakhma (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Research on the phenomenon of sexual violence against women continues to persist to this day, both in urban and rural areas, with the number of violence cases steadily increasing each year. The repercussions of these sexual violence actions are immensely grave, causing victims to experience a range of traumas. Some victims may endure mild trauma, allowing them to maintain communication with others, while others suffer severe trauma, rendering them incapable of meeting or communicating with anyone else. Some victims even withdraw into their rooms, attempt self-harm, or contemplate ending their own lives. One crucial aspect in comprehending the impact of sexual violence against women is the victims' self-concept. The primary objective of this research is to analyze the self-concept of women who have fallen victim to sexual violence, with a focus on intrapersonal communication perspectives and the self-acceptance processes of these victims. The research employs a qualitative method with a phenomenological approach, which enables researchers to delve into an understanding of the victims' experiences. The research findings reveal that the intrapersonal communication process in the four informant victims of sexual violence occurs progressively. Each informant undergoes a complex and intricate self-acceptance process. However, the conclusion drawn from this research is that the informants ultimately succeed in developing a positive self-concept despite enduring a challenging journey. Therefore, this research offers valuable insights into how victims of sexual violence respond and cope with their traumatic effects through intrapersonal communication and self-acceptance.